Malnutrition in Timor-Leste : A Review of the Burden, Drivers, and Potential Response - Provo, Anne (World Bank, Washington, DC, 2017)
This report presents the findings of nutrition assessment, gap analysis, and donor mapping exercise in the Democratic Republic of Timor-Leste (RDTL). Timor-Leste, though as a young and fragile state, has the preconditions for successful development. However, persistent high levels of malnutrition threaten to impede efforts to reduce poverty, capitalize on gains in human and skills development, increase productivity, and stimulate economic growth. Though progress has been in other areas of human development, malnutrition – particularly maternal and Child undernutrition – is the single greatest contributor to premature death and disability in the country and presents an unparalleled development challenge. In 2013, over half (50.2 percent) of all children under-five were stunted in their physical and cognitive development. Timor-Leste has the third highest stunting prevalence in the world, higher than all other g7+ countries and a significant outlier relative to its level of economic development. In 2013, nearly one in three (63.2 percent) children (6-59 months) and 2 in 5 women age 14-60 (39.5 percent) were anemic. Although the country is no longer in an emergency situation, the prevalence of wasting (11 percent) – an indicator of acute malnutrition and a prominent risk factor for child mortality – exceeds the WHO threshold for high public health significance, with emergency levels of wasting experienced in Covalima and Oecusse districts. Overweight prevalence is low relative to global averages, but has risen more than five-fold among adult women over the past decade. Though Timor-Leste does not yet suffer from the double burden of malnutrition, it will soon emerge if the problem continues unaddressed.